Distribution coefficients of trace metals between modern coral-lattices and seawater in the northern South China Sea: Species and SST dependencies. (January 2020) - Jiang, Wei; Yu, Kefu; Wang, Ning; Yang, Hua; Yang, Haodan; Xu, Shendong; Wei, Chaoshuai; Wang, Shaopeng; Wang, Yinghui
Graphical abstract: Highlights: Distribution coefficients were species dependent, indicating some biologic controls. No significant correlation between D values of metals except Cd and SST was found. Metal in coral skeleton is a reliable proxy for dissolved metal in surface seawater. Abstract: Scleractinian corals provide an excellent archive of geochemical proxies that allow the reconstruction of the oceanographic and climatic changes in the oceans. However, limited knowledge regarding the distribution coefficients ( D ) of trace metals between coral lattices and seawater has complicated efforts to obtain accurate quantitative data for seawater chemistry. Here we estimated the D values of five trace metals (Cu, Zn, Pb, Cd and Cr) for three coral species ( Favia palauensis, Porites lutea, and Pavona decussata ) and in situ seawater around Weizhou Island in the northern South China Sea. Despite several variations that could not be explained solely by species, our results were within the approved ranges of the previous reported estimates, and provide the most accurate D values for the these species to date. We also focused on the possible effects of surface seawater temperature (SST) on D vaules, finding no significant relationship. Nevertheless, the effects of SST, which could impact the distribution behavior of trace metals (especially Cd) should be paid more attention in the context of global climate change. The more precise D values for corals provided here represent important basic data for future research on coral reefs and expanded our knowledge of chemical signatures in biogenic lattices with regard to ocean composition.